Normal reference ranges for biochemical substances relating to renal, hepatic, and bone function in fetal and maternal plasma throughout pregnancy. Issue 4 (April 1985) - Moniz, C F; Nicolaides, K H; Bamforth, F J; Rodeck, C H
Abstract : Normal reference ranges for sodium, potassium, urea, creatinine, calcium, phosphate, total protein, albumin, bilirubin, alkaline phosphatase, and aspartate transaminase were determined from 344 fetal and maternal plasma samples between 15 and 38 weeks' gestation. Pure fetal blood was obtained by fetoscopy in the second trimester and in the third trimester by umbilical cord puncture at delivery. All biochemical substances were measured by continuous flow (SMAC, Technicon) except albumin, which was measured by turbidimetry (CobasBio, Roche). The resulting data were analysed on an AMDAHL 470A computer and reference ranges covering 2.5 to 97.5 percentiles were defined. Analysis of variance was performed to examine the overall effect of gestational age on the analytes measured and on the changes in the fetal compartment relative to the mothers'. A paired t test was performed to examine how these biochemical substances in fetal plasma related to maternal plasma from the same pregnancy.